Strategi Pengelolaan Non-Performing Financing Pada Keberlangsungan Usaha BPRS - Kharimatus Sholikha; Athi’ Hidayati; Peni Haryanti; Anita Musfiroh (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study was motivated by the phenomenon of the rising Non-Performing Financing (NPF) ratio at PT BPR Syariah Lantabur Tebuireng Jombang, which increased from 15.63% in 2024 to 21.36% in 2025. This percentage has exceeded the 5% safety threshold set by OJK. Nevertheless, the institution has remained capable of maintaining its total assets and business continuity. This study aims to identify the NPF management strategies in maintaining the institution’s business continuity. This study employs a qualitative method using a case study approach. Data were collected through interviews, supported by field observations and documentation. The results indicate that PT BPR Syariah Lantabur Tebuireng Jombang implements four NPF management strategies, including increasing the mobilization of low-cost funds as the primary source of financing, controlling operational costs (PPAP), and financing restructuring through rescheduling, reconditioning, and restructuring mechanisms supported by active field monitoring. These four strategies play a role in maintaining revenue stability, expenditure balance, absorption of potential losses, and liquidity risk control, thereby ensuring the institution's business continuity remains intact despite the continuous increase in NPF.